Characteristics of innovation systems that lead to greater productivity and economic development - Gutiérrez Rojas, Cristián; Smith-Uldall, Jerome; Ganga-Contreras, Francisco; González, Patricia (Revista Venezolana de Gerencia, 2024)
The national R&D system is a concept that has gained significant recognition; however, measuring it is challenging and not devoid of difficulties. In this paper the method of composite variables is applied to configure R&D systems and with this examines their characteristics and subsequent impact on fostering greater innovation by studying a group of OECD countries. Starting with many variables, 31 variables were selected for the second step and used in a factor analysis to create composite indicators or unobservable abstract variables. Each variable’s assignment to a single factor is clear, allowing the identification of five distinct and interpretable factors. Subsequently, a knowledge production function was estimated, considering a technological outcome of the R&D systems as the dependent variable; another function was configured reflecting the scientific output. Finally, an additional model was estimated, using productivity as the dependent variable. In all models, the National R&D Effort and Innovative Firms Factor emerged as the most significant variable, underscoring the importance of reaching certain thresholds in terms of available human and physical resources for carrying out innovative efforts within an R&D system.